ACUTE AND CHRONIC TOXICITY OF TAGETES ELLIPTICA (ASTERACEAE) AND DIMETHOATE ON PREDATORS AND PARASITOIDS OF AGRICULTURAL PESTS OF IMPORTANCE IN PERU - Iannacone, José (2015)
Tagetes elliptica Smith "Chincho", or "black mint sacha" is a plant used as a biocide in ecological agriculture mainly for its essential oils like cis/trans-Epoximyrcene. Dimethoate is an organophosphate insecticide with action of contact and ingestion. The aim of this study was to evaluate the acute and chronic toxicity of T. elliptica and dimethoate on six predators and parasitoids of agricultural pests from Peru. Toxicity tests for Chrysoperla externa, Ch. asoralis, Orius insidiosus, Geocoris callosulus, Trichogramma pretiosum and T. pintoi used T. elliptica and dimethoate with five concentrations plus control. Regarding acute tests with the "chincho", it was observed the following sequence from highest to lowest based on toxicity of median lethal concentration (LC50 (48 h): C. externa > T. pretiosum > C. asoralis > T. pintoi > O. insidiosus (nymph) > O. insidiosus (adult) > G. callosulus (nymph) > G. callosulus (adult). In exchange for dimethoate was: T. pintoi > T. pretiosum > C. externa > C. asoralis > O. insidiosus (adult) > O. insidiosus (nymph) > G. callosulus (adult) > G. callosulus (nymph). In relation to chronic tests with "chincho" decreasing the following sequence was observed lower toxicity: C. externa> C. asoralis > T. pintoi > T. pretiosum. Finally, for dimethoate: C. externa > C. asoralis > T. pretiosum > T. pintoi. Dimethoate showed harmful effects on the six species of beneficial insects compared to the "chincho" that was less risky.